2018
DOI: 10.1111/jre.12576
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase‐plasminogen activator protects periodontal ligament fibroblast from oxidative induced‐apoptosis and DNA damage

Abstract: The present study brings support to the theory that uPA may have a protective role for periodontal tissue and could protect PDL fibroblasts from oxidative DNA damage and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Amilorides hold a singular place in the history of cell physiology, providing a set of structurally-related analogs that can inhibit several different biological targets [28]. However, numerous studies have attributed pharmacological effects to a specific target of interest following treatment with amiloride or an analog without consideration of possible off-target effects [41][42][43]. In the cancer field alone, there are a several examples whereby effects have been ascribed to inhibition of either uPA [44][45][46] or NHE1 [47][48][49] without controlling for possible effects from the other target.…”
Section: Discussionmentioning
confidence: 99%
“…Amilorides hold a singular place in the history of cell physiology, providing a set of structurally-related analogs that can inhibit several different biological targets [28]. However, numerous studies have attributed pharmacological effects to a specific target of interest following treatment with amiloride or an analog without consideration of possible off-target effects [41][42][43]. In the cancer field alone, there are a several examples whereby effects have been ascribed to inhibition of either uPA [44][45][46] or NHE1 [47][48][49] without controlling for possible effects from the other target.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-II exerts neuroprotective effects by reducing oxidative stress through the acceleration of the Nrf2-nuclear translocation and by improving mitochondrial function 46 , 47 . Urokinase-plasminogen activator inhibits oxidative stress-induced apoptosis and DNA damage 48 . STC1 improves brain dysfunction after cerebral irradiation in rats by increasing CAT activity in the hippocampus 49 .…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition to direct damage and induced inflammation, oxidative stress can cause genetic mutations and PDLSC apoptosis through DNA damage. 22 Moreover, diabetes-induced oxidative stress can cause telomere dysfunction and PDLSCs senescence, which dampens periodontal bone tissue regeneration and reconstruction, and ultimately exacerbates bone loss in periodontitis. 23 Sun et al recently reported that increased mitochondrial ROS, impaired mitochondrial function, and compromised mitochondrial biogenesis in diabetes could aggravate the severity of periodontitis.…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Proved/potential mechanisms that mediate the detrimental effects of lipotoxicity on diabetes-associated periodontitis. M: Greater ROS levels and oxidative stress markers in crevicular fluid 20,23,26,27 M: Impaired mitochondrial function in periodontium cells 24 M: Lower Nrf2 level in periodontal tissues 24,25 O: Increased PDLSCs apoptosis, 24 senescence and telomere dysfunction 23 O: Increased bone resorption [23][24][25] Clinical 19,20,26,27 In vivo 21,22,24 In vitro 21,[23][24][25] ER stress M: Greater UPR-related gene expression and impaired ER function in periodontal tissues [36][37][38]108 In vivo 34,35,37,38,108 In vitro 34,36 Inflammation M: Inflammatory destruction of the supporting tissues around the teeth and an aberrant host response 39 M: Greater IL-1β and IL-18 in the gingival crevicular fluid and the activation of NLRP3 in gingival tissue 40 M: Greater expression of CD36 in macrophages and gingival fibroblasts a46-48 O: Increased osteoclast formation and inflammatory cytokine production a47-51 O: Increased bone resorption 47,48,50 Clinical 40,47 In vivo 39,46,49,…”
Section: Ta B L Ementioning
confidence: 99%